PENGGUNAAN MODEL KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Firman; Desyandri; Ranianisa Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study was to determine whether or not the cooperative model of the Make A Match type affected the learning outcomes of fourth grade students in social studies learning. The type of research applied is an experiment with a true experiment design, in the form of a pretest-posttest control group. The class IV samples at SDN 06 Piai Tangah and class IV at SDN 07 Piai Tangah were selected using a random cluster technique. The results of the study show that the cooperative model of the Make A Match type has an effect on social studies learning outcomes for fourth grade students with a t-count score (4.9045) > t-table (1.697).